Autologous serum eye drops for ocular surface disorders. Issue 5 (October 2021) - Cui, David; Li, Gavin; Akpek, Esen K.
Abstract : Purpose of review: Ocular surface disease is a prevalent, diverse group of conditions that cause patient discomfort and decreased visual acuity and present considerable expense to both patients and healthcare systems. Autologous serum eye drops are a topical treatment modality derived from the patient's own blood. Use of serum eye drops for ocular surface disease has been promising due to biochemical similarities to endogenous tears. Recent findings: Use of serum eye drops for moderate to severe ocular surface diseases such as dry eye, corneal epithelial defects, and inflammatory conditions has become more prevalent. Recent studies have demonstrated that the use of serum eye drops is well-tolerated by patients and associated with improvement in patient-reported outcomes and objective dry eye parameters. Production of serum eye drops may vary, treatment costs can be significant, and the quality of evidence for serum eye drop use published from randomized controlled trials is modest, particularly for long-term treatment. Accessibility remains an area for improvement and may be complemented by allogeneic serum eye drops. Summary: Serum eye drops are frequently used as a safe, well-tolerated, and effective treatment for ocular surface disease. Further research is needed to assess long-term outcomes and improve accessibility.